Maize Price Volatility : Does Market Remoteness Matter? - Moctar, Ndiaye; Elodie, Maitre d’Hôtel; Tristan, Le Cotty (World Bank Group, Washington, DC, 2015)
This paper addresses the role of market remoteness in explaining maize price volatility in Burkina Faso. A model of price formation is introduced to demonstrate formally that transport costs between urban and rural markets exacerbate maize price volatility. Empirical support is provided to the proposition by exploring an unusually rich data set of monthly maize price series across 28 markets over 2004-13. The methodology relies on an autoregressive conditional heteroskedasticity model to investigate the statistical effect of road quality and distance from urban consumption centers on maize price volatility. The analysis finds that maize price volatility is greatest in remote markets. The results also show that maize-surplus markets and markets bordering Côte d'Ivoire, Ghana and Togo have experienced more volatile prices than maize-deficit and non-bordering markets. The findings suggest that enhancing road infrastructure would strengthen the links between rural markets and major consumption centers, thereby also stabilizing maize prices.